Native-Like Performance of Pragmatic Features: Speech Acts in Spanish - Vacas Matos, Marta; Cohen, Andrew D (Contrastive Pragmatics, 2022)
Abstract This study had as its goal to investigate how nonnative speakers (NNSs) of Spanish were able to perform pragmatics which in various ways resembled that of native speakers (NSs). The study focused on three advanced NNSs of Spanish who had contributed data six years earlier to a corpus of NS and NNS speech acts of complimenting, apologizing and refusing. The purpose was to do a contrastive analysis comparing the pragmatic performance of NNSs and NSs in order to capture both similarities and areas where highly competent NNSs displayed knowledge gaps, however subtle. The subjects responded to a language background questionnaire regarding their learning of Spanish and also completed a learning style preference survey. They were then asked to revisit their earlier performance in pragmatics from the corpus data and to describe the strategies that they used to produce their highly-rated performance in Spanish pragmatics at that time. The findings revealed ways in which the three subjects differentially imitated NS behavior, and provided insights as to how they arrived at native-like behavior in their facial expressions, use of clicks, physical contact practices, colloquial language, and cursing. The subjects' reported learning style preferences appeared to be generally consistent with the strategies that they reported using for dealing with the pragmatic features of interest, such as the way that they dealt with cursing.